Differential Gene Expression Induced by Different TLR Agonists in A549 Lung Epithelial Cells Is Modulated by CRISPR Activation of TLR10 - Špela Knez; Mojca Narat; Jernej Ogorevc (Biomolecules, 2022)
Toll-like receptor 10 (TLR10) is the only member of the TLR family whose function and ligand have not been clearly described. Literature reports on its function are contradictory and suggest a possible immunomodulatory role that depends on the cell type, the pathogen, and the level of TLR10 expression. To investigate the regulatory role of TLR10 in A549 lung epithelial cells, we overexpressed TLR10 using CRISPRa technology and examined the differential expression of various genes involved in TLR signaling activated by different TLR ligands, namely dsRNA, LPS, and Pam3Cys. The expression of proinflammatory cytokines, such as IL1β, IFNβ, TNFα, IL8, CXCL10, and CCL20, decreased in the challenged cells overexpressing TLR10, whereas the expression of the anti-inflammatory cytokine IL10 and the antimicrobial peptide hβD-2 increased. For several of the regulated inflammatory markers, we were able to show the change in gene expression was translated to the protein level. It appears that TLR10 can function as an anti-inflammatory in A549 cells, depending on its expression level and that the mode of action may be virulence factor-specific. The potential suppression of inflammation by regulating expression of TLR10 in lung epithelial cells may allow the development of new approaches to balance an inflammatory response and prevent extensive tissue damage in respiratory diseases.